PERBANDINGAN EFEKTIVITAS PENGGUNAAN MEDIA NEARPOD DAN EDPUZZLE DALAM MENINGKATKAN HASIL BELAJAR MATERI PENDAPATAN NASIONAL KELAS XI IPS 2 SMAS AL- IZHAR JAKARTA - Supriyanto Supriyanto (CV Sintesia, 2023)
This research aims to evaluate the effectiveness of Nearpod and Edpuzzle in improving XI IPS ‘s learning outcome in SMA Al-Izhar Jakarta. The methods used in this paper is the class action research for 19 students. The research was conducted in 2 cycles–each has 4 phases which are planning, action, observation, and reflection. The datas are collected through tests and questionnaires. The Data was analysed by using quantitative descriptive technique. It can be concluded that the use of Nearpod and Eduzzle can boost the student’s result. This is proven to be true by the increasing average score in the first cycle 5,72% to 15,54% in the second cycle. Edpuzzle was proven to be more effective compared to Nearpod because it brought such increasement in the second cycle up to 15,54% with the classical coverage score reached to 84,21%